Proceedings of Proceedings of the Corfu Summer Institute 2015 — PoS(CORFU2015) 2016
DOI: 10.22323/1.263.0159
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotically safe inflation from quadratic gravity

Abstract: Asymptotically Safe theories of gravity have recently received much attention. In this work we discuss a class of inflationary models derived from quantum-gravity modification of quadratic gravity according to the induced scaling around the non-Gaussian fixed point at very high energies. It is argued that the presence of a three dimensional ultraviolet critical surface generates operators of non-integer power of the type R 2−θ/2 in the effective Lagrangian, where θ > 0 is a critical exponent. The requirement o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 36 publications
(49 reference statements)
1
16
0
Order By: Relevance
“…In a first approximation, it has been shown that the anti-screening character of the Newton coupling could replace the classical initial singularity with a regular bounce or with an emergent universe scenario [62], both characterized by a non-vanishing minimum value of the scale factor and a period of inflation following the bounce. Finding the class of actions giving rise to this type of regular cosmologies is the first step towards understanding the relation between the results obtained in [30,37] and summarized in these proceedings, and the inflationary scenario following a cosmological bounce [62]. We reserve to discuss these problems in future works.…”
Section: The Inflationary Mechanism In Asymptotically Safe Gravitymentioning
confidence: 96%
See 2 more Smart Citations
“…In a first approximation, it has been shown that the anti-screening character of the Newton coupling could replace the classical initial singularity with a regular bounce or with an emergent universe scenario [62], both characterized by a non-vanishing minimum value of the scale factor and a period of inflation following the bounce. Finding the class of actions giving rise to this type of regular cosmologies is the first step towards understanding the relation between the results obtained in [30,37] and summarized in these proceedings, and the inflationary scenario following a cosmological bounce [62]. We reserve to discuss these problems in future works.…”
Section: The Inflationary Mechanism In Asymptotically Safe Gravitymentioning
confidence: 96%
“…(9), the form of the deviation δL RG ≡ f RG (R) depends crucially on the running of the gravitational couplings. Therefore, the study of the inflationary scenario arising from the RG-improvement of the Einstein-Hilbert action might actually put constraints on microscopic details of the theory, as for instance its critical exponents [30,37]. Moreover, the nearly-scale invariant power spectrum of temperature anisotropies in the CMB might be related to the deviation of the Lagrangian L eff grav from the scale-invariant regime described by L * .…”
Section: Running Couplings and Effective Actionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Bonanno and Platania [60,111], a class of inflationary models arising from the RG improvement of quadratic gravity (without matter) has been investigated [see also [48,92]]. According to the studies of the non-perturbative RG flow of truncated f (R)theories without matter [104,112], the NGFP is attractive with respect to three relevant directions, those associated with the dimensionless couplings (g k , λ k , β k ), with β k = B(k)/G(k) [26,34,80,81].…”
Section: Comparison With the Planck Data In Rg-improved Quadratic Gravitymentioning
confidence: 99%
“…According to the studies of the non-perturbative RG flow of truncated f (R)theories without matter [104,112], the NGFP is attractive with respect to three relevant directions, those associated with the dimensionless couplings (g k , λ k , β k ), with β k = B(k)/G(k) [26,34,80,81]. The question motivating the studies in Bonanno and Platania [60,111] is whether the scale dependence of all relevant gravitational couplings can modify the classical Starobinsky model and if the RG-improved model is compatible with the Planck data. The ansatz for the gravitational action is Pl associated with the fixed-point action S * grav , Equation (46), is also shown for comparison.…”
Section: Comparison With the Planck Data In Rg-improved Quadratic Gravitymentioning
confidence: 99%